"Quem não reagiu, está vivo": o ativismo do o poder executivo paulista nas políticas para contenção da letalidade policial - Andrade, Fabiane Penedo De [UNIFESP] (2019)
This research had as objective to present the performance of the executive power of São Paulo in public security policies to contain police lethality between 1996 and 2015. As methodology, the bibliographic research techniques were used in order to base the theoretical foundation related to both the field (public problem, agenda formation, policy formulation, moral entrepreneurship, incremental policies and state inaction). A documentary analysis was also carried out, which analyzed the laws, regulations and normative regulations produced, above all, by the State Secretariat of Public Security of São Paulo, as well as documents prepared by federal government agencies, reports and documents produced by nongovernmental Brazilian civil society, international organizations and think tank institutions. The considerations that come to the end of the research is that all the activism of the executive government of São Paulo was insufficient to contain the deaths committed by police, either because, on the one hand, the government's discourse was of approval and legitimation of police lethality, because the policies implemented were incremental, reinforcing only investigative mechanisms already present in Brazilian legal systems and ineffective in their objectives.